2018
DOI: 10.3390/met8110893
|View full text |Cite
|
Sign up to set email alerts
|

On the Microstructures and Fatigue Behaviors of 316L Stainless Steel Metal Injection Molded with Gas- and Water-Atomized Powders

Abstract: 316L stainless steel samples are fabricated by metal injection molding using water-atomized and gas-atomized powder with different oxygen contents. The influences of oxygen on the microstructural evolution and fatigue properties of the samples are investigated. The oxygen tends to react with Mn and Si to form oxide particles during sintering. The oxides hamper the densification process and result in decreased sintered density. Moreover, their existence reduces the Mn and Si dissolving into the base metal and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 34 publications
3
13
0
Order By: Relevance
“…Finally, a comparison of the tensile performance of 3-D printed 316 L stainless steel samples manufactured with different techniques is presented in Table 1. It can be observed that Flat and On-edge sintered samples depicted similar tensile strength and stiffness values to those obtained by MIM process based on a similar sintering stage (Zhang et al, 2018;Agarwala et al, 1996;Yoon et al, 2003). In addition, 3-D printed SLS samples showed elongation to fracture values of 24%-42% for porosity levels between 1% and 2%, that are in accordance with the results obtained in this study (Suryawanshi et al, 2017;Kong et al, 2018;Li et al, 2019), and they are comparable, and even improving in certain cases, with published recent studied based on FFF technique (Gong et al, 2019;Damon et al, 2019).…”
Section: Resultssupporting
confidence: 56%
See 2 more Smart Citations
“…Finally, a comparison of the tensile performance of 3-D printed 316 L stainless steel samples manufactured with different techniques is presented in Table 1. It can be observed that Flat and On-edge sintered samples depicted similar tensile strength and stiffness values to those obtained by MIM process based on a similar sintering stage (Zhang et al, 2018;Agarwala et al, 1996;Yoon et al, 2003). In addition, 3-D printed SLS samples showed elongation to fracture values of 24%-42% for porosity levels between 1% and 2%, that are in accordance with the results obtained in this study (Suryawanshi et al, 2017;Kong et al, 2018;Li et al, 2019), and they are comparable, and even improving in certain cases, with published recent studied based on FFF technique (Gong et al, 2019;Damon et al, 2019).…”
Section: Resultssupporting
confidence: 56%
“…The FFF technique generates a 3-D object through the deposition of a thermoplastic extruded filament. Furthermore, additive manufacturing of metals becomes increasingly important in many industrial fields (Gonzalez-Gutierrez et al, 2018;Zhang et al, 2018;Suryawanshi et al, 2017;Liverani et al, 2017;Kong et al, 2018). However, the current use of AM processes, such as laser-based powder bed fusion techniques, are quite complex and expensive to purchase and operate (Thompson et al, 2019;Gong et al, 2019;Damon et al, 2019;Gonzalez-Gutierrez et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During sintering, the residual oxygen content of SS 316L tends to react with alloying elements and form oxides in the sintered parts, and the presence of oxides may impede densification during sintering. 27 Powders with lower oxygen content have better sinterability and result in higher densification. 28 During sintering of 316L, oxides containing Mn and Si are more likely to be formed due to the lower DG (Gibbs free energy) of their oxidation reactions.…”
Section: Chemical Composition Of Powdersmentioning
confidence: 99%
“…Moreover, the formation of SiO 2 and MnO reduces the amount of Si and Mn elements, which are essential contributors to the strengthening of the alloy, 29 thus leading to inferior tensile and ductility properties. 27 The formation of Si and Mn oxides during the LPBF process could enhance the mechanical properties 30 but may have detrimental effects on the densification of the sintered parts. Varying amounts of oxides may be present in the BJT parts, depending on the oxygen content.…”
Section: Chemical Composition Of Powdersmentioning
confidence: 99%